VALUASI EKONOMI KAYU DAN KESEJUKAN KAWASAN ARBORETUM UNIVERSITAS RIAU - Pardo Abastama; Evi Sri Sribudiani; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Forest has such great benefits for life. Various tangible and intangible benefit that can be obtained from the forest can also be optained from the arboretum. Although basicly arboretum serves as a means of education. Tangible and intangible benefits that could potentially be produced is still rate as low, causing excessive exploitation. Assessment the benefits of trees on a place at the price of economic value necessary to considen improve the bargaining position and transforming into economic value of money. The presence of trees also affect the micro climate (value coolness) around the arboretum. Becomes a problem when the arboretum was damaged because it was not able to provide coolness around the arboretum. The research was conducted in the arboretum area of Riau University Pekanbaru on December 2015. The purpose of this research was to determine the economic value of trees in the arboretum area of Riau University and determine the economic value of the coolness in the arboretum area of Riau University. The research result showed that the economic value of wood in Riau University arboretum is Rp. 951.852.785,54 and the economic value of coolness in Riau University arboretum is Rp 23.875.000.000.Keywords:Economic valuation of wood, the coolness, arboretum